Gender-Neutral Language in Societal Perception: Negotiating Inclusion and Controversy - Heru Saputra (Insan Kreasi Media, 2025)
Gender identity and social impressions are greatly shaped by language, which also is crucial. Gender-neutral language's emergence seeks to support inclusivity and fit non-binary identities. This paper investigates society opinions, debates, and difficulties with gender-neutral terminology. It looks at how gender identity representation is shaped by language patterns and the elements causing acceptance or opposition. It also looks at how legislation and the media shape public perceptions and their contributions to either supporting or impeding language reform. This study examines scholarly literature, policy documents, and media reports using a library research approach. By means of case studies from many linguistic backgrounds, a qualitative study reveals recurrent themes in gender-neutral language acceptance and opposition, therefore evaluating the efficacy of media advocacy and policy implementation. The esults show that even if younger generations are embracing gender-neutral language more and more, institutional and cultural barriers cause opposition. The paper emphasises how media helps to normalise inclusive language and the influence of government actions in either supporting or hindering their acceptance. The study finds that reconciling inclusivity with cultural traditions depends on collaborative efforts among policymakers, educators, media, and language institutions.